2012
DOI: 10.1186/1742-4755-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the prevalence of periodontal disease in low-risk pregnant women

Abstract: ObjectiveTo evaluate the prevalence of periodontal disease (PD) among Brazilian low-risk pregnant women and its association with sociodemographic factors, habits and oral hygiene.MethodThis cross-sectional study included 334 low-risk pregnant women divided in groups with or without PD. Indexes of plaque and gingival bleeding on probing, probing pocket depth, clinical attachment level and gingival recession were evaluated at one periodontal examination below 32 weeks of gestation. Independent variables were: ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
125
8
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(156 citation statements)
references
References 33 publications
9
125
8
14
Order By: Relevance
“…[95] Other previous studies reported а positive relationship between obesity & the severity and prevalence of periodontitis. [ 96,36,97,98,35] In the same line this, results agreed with Haffajee & Socransky 2009, who noted in the subgingival biofilms of periodontal healthy, overweight & obese individuals, suggesting а higher ƁΜӀ may contribute to periodontitis initiation & progression. The likelihood of developing the periodontаl disease in overweight & obese individuals, respectively, was 27% & 81% higher than in individuals with normal weight and а strong association between periodontal disease & obesity.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…[95] Other previous studies reported а positive relationship between obesity & the severity and prevalence of periodontitis. [ 96,36,97,98,35] In the same line this, results agreed with Haffajee & Socransky 2009, who noted in the subgingival biofilms of periodontal healthy, overweight & obese individuals, suggesting а higher ƁΜӀ may contribute to periodontitis initiation & progression. The likelihood of developing the periodontаl disease in overweight & obese individuals, respectively, was 27% & 81% higher than in individuals with normal weight and а strong association between periodontal disease & obesity.…”
Section: Discussionsupporting
confidence: 81%
“…[101] Vogt et al, (2012) reported that, the prevalence of periodontаl disease was 47%. [35] Increased tooth mobility has been detected in pregnancy even in periodontal healthy women. [63] The upper incisors are most mobile during the last month of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although half of low-risk pregnancies are likely to have periodontal disease and bacterial flora, which can be associated with poor pregnancy outcomes [33,34], our patient participants reported that oral health care was the least discussed health behavior in obstetric officeS. Unfortunately, a previous study suggests that first time pregnant patients have little oral health knowledge [35].…”
Section: Discussion and Conclusion Discussionmentioning
confidence: 76%